Gender Differences in Peer Recognition by Economists. Issue 5 (20th October 2022) - Card, David; DellaVigna, Stefano; Funk, Patricia; Iriberri, Nagore
Abstract : We study the selection of Fellows of the Econometric Society, using a new data set of publications and citations for over 40, 000 actively publishing economists since the early 1900s. Conditional on achievement, we document a large negative gap in the probability that women were selected as Fellows in the 1933–1979 period. This gap became positive (though not statistically significant) from 1980 to 2010, and in the past decade has become large and highly significant, with over a 100% increase in the probability of selection for female authors relative to males with similar publications and citations. The positive boost affects highly qualified female candidates (in the top 10% of authors) with no effect for the bottom 90%. Using nomination data for the past 30 years, we find a key proximate role for the Society's Nominating Committee in this shift. Since 2012, the Committee has had an explicit mandate to nominate highly qualified women, and its nominees enjoy above‐average election success (controlling for achievement). Looking beyond gender, we document similar shifts in the premium for geographic diversity: in the mid‐2000s, both the Fellows and the Nominating Committee became significantly more likely to nominate and elect candidates from outside the United States. Finally, we examine gender gaps in several other major awards for U.S. economists. We show that the gaps in the probability of selection of new fellows of the American Academy of Arts and Sciences and the National Academy of Sciences closely parallel those of the Econometric Society, with historically negative penalties for women turning to positive premiums in recent years.